Exploring market orientation, innovation, and financial performance in agricultural value chains in emerging economies - Khanh Le Phi Ho; Chau Ngoc Nguyen; Rajendra Prasad Adhikari; Morgan P. Miles; Laurie Bonney (Journal of Innovation & Knowledge (JIK), 2018)
This study explored the usefulness of market orientation in an agricultural value chain in an emerging economy: Vietnam. Drawing on data from 190 actors in a beef cattle value chain in Vietnam's Central Highlands, the study examined the relationship between market orientation and innovation. The findings indicate that there is no significant relationship between market orientation and performance. However, customer orientation and inter-functional coordination are positively related to innovation, and there is a positive relationship between innovation and financial performance. The findings provide insight into the relationships among market orientation, innovation, and performance in agricultural value chains in emerging economies.
Keywords: M3; Q1; P3; 650; Beef cattle; Market orientation; Innovation; Performance; Emerging economy